TEACHING STRATEGIES TO MOTIVATE STUDENTS IN SPEAKING CLASS USING SONGS (EVIDENCE FROM SMK SEHAT INSAN PERJUANGAN MOJOAGUNG JOMBANG) - Yusuf, Adi; Paramita, Yuli (IAIN Surakarta, 2024)
This study aims to identify the strategies of drilling and creative tasks used by a teacher and how the teacher applies these strategies to motivate students to speak in class. A qualitative research design was used to answer this study's questions. To collect the data, this study used interviews and classroom observations as the instruments. The participant in this study was one of the English language teachers in SMK Sehat Insan Perjuangan Mojoagung Jombang, where the teacher has been teaching for five years. The results indicated that the teacher used drilling and creative tasks with songs booming on TikTok and other social media related to materials containing moral values to motivate students to speak in class. The use of drilling as a teaching strategy was presented by asking students to say the words that had been spoken by the teacher repeatedly. While the creative task as a teaching strategy was depicted by the given stimulus in the form of a task, the students were asked to present the task result in front of the class, and the other were asked to respond. The results show that using drilling and creative tasks as learning strategies can make students more active in speaking, and this was evidenced by those who were usually just silent and passive in the speaking class getting increased confidence, improved fluency, and a greater willingness to get involved in the class.